Development of fish snack (Keropok) with sodium reduction using alternative salts (KCl and CaCl2) - Passakorn Kingwascharapong; Pranpriya Paewpisakul; Wilaiwan Sripoovieng; Sasina Sanprasert; Jaksuma Pongsetkul; Ratiwan Meethong; Kanrawee Hunsakul; Supatra Karnjanapratum; Ali Muhammed Moula Ali; Kantiya Petsong; Saroat Rawdkuen (My University, 2023)
The incidence of non-communicable diseases (NCDs) caused by excessive sodium intake is becoming an important issue that many researchers have investigated. Processing is an effective way to add value to underutilized fish species. Thus, the objective of this research was to develop a fish snack (Keropok) using reduced sodium. Two types of alternative sodium chloride (NaCl) were used, namely potassium chloride (KCl) and calcium chloride (CaCl2) with substitution at levels of 15, 30, and 45% (w/w). The results indicated that substitution of NaCl with KCl or CaCl2 in the product had a negative effect on the cooking yield (%) (P<0.05). Using 55% NaCl with 45% KCl (B3) in Keropok had a consumer acceptance score similar to the control formula (P>0.05) and the lowest sodium content (P<0.05). After storage at 4°C for 21 days, the microbial loads (Bacillus cereus, Escherichia coli, mold, Staphylococcus aureus, yeast) in B3 satisfied the requirements of the Thailand Community Product Standard (107/2011). In addition, increasing the storage time did not affect the texture of the product (hardness, gumminess, chewiness and cohesiveness) nor consumer acceptance (P>0.05). B3 was rich in nutrients (macromolecules and micromolecules) that are essential to the human body. Therefore, Kerepok (55% NaCl with 45% KCl: B3) could be considered as a healthy snack.
Keywords: Chewiness; Sodium Intake and Health